Relationship between the physician-based clinical scale for foot and ankle surgery and patient-reported outcomes in patients with long-standing rheumatoid arthritis: Results from a multicenter prospective observational cohort study. Issue 3 (4th May 2021) - Kojima, Toshihisa; Ishikawa, Hajime; Tanaka, Sakae; Haga, Nobuhiko; Nishida, Keiichiro; Yukioka, Masao; Hashimoto, Jun; Miyahara, Hisaaki; Niki, Yasuo; Kimura, Tomoatsu; Oda, Hiromi; Asai, Shuji; et al.
Abstract: Objectives: To validate and establish targets for the physician-based clinical scale for foot surgery in rheumatoid arthritis (RA) patients based on patient-reported outcomes from a multicenter prospective cohort. Methods: We collected data on demographics, values from the RA foot and ankle scale by the Japanese Society for Surgery of the Foot (JSSF-RA), and patient-reported outcomes (PROs) including the Health Assessment Questionnaire Disability Index (HAQ-DI) before (baseline) and 6 and 12 months after joint surgery. Target values for JSSF-RA were determined according to the lower limit of the 95% CI of JSSF-RA in patients with HAQ-DI ≤0.5 after adjusting for age and sex. We used multiple linear regression analysis to examine potential predictors of JSSF-RA target achievement at baseline. Results: Cross-sectional analysis was conducted on data from 417 cases. The JSSF-RA target for foot and ankle surgery was set at 74 according to the JSSF-RA value corresponding to HAQ-DI ≤0.5 (mean 77.6, 95% CI: 74.3–80.9). Longitudinal analysis of patients who underwent foot surgery ( N  = 59) determined target cut-off values of 1.188 and 65 for HAQ-DI and JSSF-RA at baseline, respectively, as being predictive for achieving JSSF-RA ≥74 after surgery. Conclusions: A JSSF-RA value of 74 represents an important target for patients with RA who have undergone foot surgery. In order to achieve this target, the timing of the surgery should be considered in the treatment of established RA patients.